Student engagement & partnering for employability skills development - Ebiringa, Thaddeus Oforegbunam; Chinemerem, Ekwenwa Kevin; Ebiringa, Ifeyinwa Edith (Serbian Journal of Management, 2015)
This study is motivated by the current high rate of graduates’ unemployment in Nigeria, occasioned by poor exposure of students to practical entrepreneurial skills development. The objective is to develop a tripartite partnering (public institutions, private institution and the students) model for employability skills development in Nigerian universities. The paper employed survey method for data collection and non-parametric statistics for exploration of entrepreneurial perception of 480 students’ drawn from eight universities in the South East and South regions of Nigeria. The result shows that students that engaged in practical and collaborative entrepreneurial extra curricula activities have had opportunities to be mentored by experienced entrepreneurial minded academic and business leaders. The out-of-classroom experiences equipped them with critical personality traits and business management skills favourable to entrepreneurial venturing upon graduation. Unfortunately, this is not the case for students who are not involved in such extra curricula entrepreneurial activities.